The Role of Islamic Psychospiritual in Building Self-Resilience of Cancer Caregivers - Norwahizatul wahed; Che Zarrina Sa`ari; Sharifah Basirah Syed Muhsin; Siti Sarah Ahmad; Mohd Syukri Zainal Abidin; Syed Mohammad Hilmi Syed Abdul Rahman (UIN Sunan Gunung Djati Bandung, 2023)
The global community is increasingly recognizing the integration of health science with religion and spirituality. In Malaysia, the field of Islamic psychospiritual science, which combines psychology with spirituality and Islamic teachings, has garnered significant research attention, particularly in addressing the challenges faced by cancer caregivers. These caregivers, often referred to as